Efficacy of structural homoloques and isomers of pralidoxime in reactivation of immobilised acetylcholinesterase inhibited with sarin, cyclosarin and soman - Hoskovcova, Monika; Halamek, Emil; Kobliha, Zbynek (Neuro endocrinology letters, 2009)
OBJECTIVES: Quantification of efficacy of monopyridinium isomers and homologs derived from clinically used Pralidoxime within reactivation of acetylcholinesterase inhibited with organophosphorus nerve agents. METHODS: This work uses the colorimetric biosensor called Detehit - cotton cloth with immobilized enzyme acetylcholinesterase. Biosensor is based on the modificated Ellman's method. RESULTS: The highest reactivation was observed with sarin-inhibited acetylcholinesterase. Substantially lower reactivation was found with the cyclosarin-inhibited enzyme whereas AChE, inhibited by soman could not be effectively reactivated under the given conditions (enzyme inhibition for 2 minutes and subsequent treatment with the reactivator for 15 minutes). CONCLUSION: Our work gives comparison of efficacy of reactivators in dependence on the length of alkylene chain and position of aldoxime functional group. Evaluation of effectivity of aldoxime reactivators is provided by simple means. The method allows rapid in vitro evaluation of the reactivators without being disturbed by excess of the organophosphate or reactivator.
Keywords: enzymy imobilizované; oximy; Soman; Biosensing Techniques; Pralidoxime Compounds; Oximes; organofosforové sloučeniny; soman; biosenzitivní techniky; cholinesterasové inhibitory; sarin; acetylcholinesterasa; Isomerism; Acetylcholinesterase; Organophosphorus Compounds; reaktivátory cholinesterasy; Cholinesterase Reactivators; Sarin; pralidoximové sloučeniny; isomerie; Enzymes, Immobilized; Cholinesterase Inhibitors